Teknologi Tepat Guna Pembuatan Batu Bata Di Desa Pematang Sijonam Kecamatan Perbaungan - Naibaho, Penteris Rumissar Panurisma; Hestukoro, Soni; Sitorus, Melvin Bismark Hamonangan; Akhiruddin, Akhiruddin (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2023)
The brick-making business in Pematang Sijonam village, Perbaungan subdistrict, already uses a mechanical system but still uses a labour-intensive system. The process of printing bricks while using a brick printing machine operated by two operators and equipment that was almost obsolete were the obstacles faced by the partners during the survey by the implementing team. The output of this service is a new brick printing machine that can be operated by only one operator so that it can increase work efficiency in brick making. This dedication succeeded in overcoming the obstacles faced by brick-making entrepreneurs in terms of brick-making. There is efficiency in terms of the use of labor to operate the brick-making machine where initially 2 people became 1 person, besides that the speed of moving the printed bricks to the drying location has increased.